Structural analysis and immunogenicity of Pseudomonas aeruginosa immunotype 2 high molecular weight polysaccharide. - Pier, G B (1986)
We analyzed high molecular weight polysaccharide (PS) from the Fisher immunotype 2 (IT-2) strain of Pseudomonas aeruginosa for molecular composition and structure, then determined its immunogenicity in healthy adults. The PS was composed of 2-acetamido-2,6-dideoxygalactose (N-acetyl fucosamine) and glucose in a molar ratio of 2:1. Structural analysis by carbon-13 and proton nuclear magnetic resonance confirmed that the high molecular weight PS was structurally identical to that of the O-specific side chain of the lipopolysaccharide. PS differed from this material in molecular size. Immunization of 19 adult volunteers with doses of 50-100 micrograms of PS resulted in significant rises (P less than 0.04-P less than 0.0001) in binding antibody levels and killing antibody titers 2 and 4 wk postimmunization. The only reaction to the vaccine was localized tenderness at the immunization site. Analysis of the immunoglobulin isotype response to the vaccine showed a rise in specific serum IgG and IgA antibodies. Heterologous responses to other P. aeruginosa PS antigens were not seen. The antibody levels attained by vaccination were comparable with those in acute-phase serum samples of patients who survived sepsis with IT-2 P. aeruginosa and were significantly higher (P less than 0.03) than specific antibody levels in bacteremic patients who died. These results confirm that PS is a high molecular weight, immunogenic form of the P. aeruginosa IT-2 serotype antigen, eliciting levels of type-specific antibody comparable with those seen among patients surviving an episode of P. aeruginosa sepsis.